Catalytic Asymmetric Cascade Dearomatization of Tryptamines with Indol-3-ylmethanols: Diastereo- and Enantioselective Synthesis of Structurally Complex Indole Derivatives - Jiang, Fei; Zhang, Yu-Chen; Yang, Xue; Zhu, Qiu-Ning; Shi, Feng (Synlett, 2016)
A chiral phosphoric acid-catalyzed asymmetric cascade dearomatization reaction of tryptamines with indol-3-ylmethanols has been established. This not only realized the first catalytic asymmetric cascade substitution of indol-3-ylmethanols, but also provided an efficient and stereoselective method (99% yield, >95:5 dr, 95:5 er) for constructing complex pyrroloindoline-based skeletons with three contiguous stereogenic centers, two of which were all-carbon quaternary centers.
Keywords: dearomatization; asymmetric catalysis; tryptamines; indoles; cascade reactions; organocatalysis